Helping Donors to Empty their Pockets: A Guide for an Ethical Organization - Laureano, Raul M. S.; Abreu, M. E. (4th Symposium on Ethics and Social Responsibility Research, 2017)
Charitable donations are an increasingly form for the sustainability of nonprofit organizations and these organizations do carry on different programs for reaching donations. Besides, ethical behaviour perceived by the donors of a non-profit or-ganization is been under the surveillance as a core driver of the donor behaviour towards the organization. Organizations do carry on communication programs us-ing Internet tools to promote the ethical behaviour within its stakeholders. The investigation examines the role of the perceived ethical behaviour of a non-profit organization in donors behaviour. Moreover, this study wants to identify the demographic traits of the donors perception the ethical behaviour of the or-ganization. The behaviour of the prospective donor is measured in four ways: i) giving or not giving; ii) the frequency of donations; iii) (average) donation amount; iv) inten-tion to donate, and the ethical behaviour is reached by an agreement scale. A questionnaire was presented to a sample of 154 respondentes registered in the da-tabases of the organization. On a general level, the findings suggest that donor’s perception of ethical behav-iour are related to donations. And every single organization is challenged to use the right and even more information concerning their ethical behaviour and, ac-cordingly, increasing their donations Dynamics.